Effect of Welding Speed on Aspect Ratio of Hastelloy X Weldment by Keyhole Plasma Arc Welding (K-PAW). (2020) - Sathishkumar, M.; Manikandan, M.; Subramani, P.; Anbarasan, N.; Jerome, S.; Arivazhagan, N.
Abstract: The formation of hot cracks in the hastelloy X weldment is a major issue in the arc welding processes. This can be resolved by the proper selection of welding parameters and higher energy density methods like plasma arc welding. The keyhole plasma arc welding (K-PAW) of hastelloy X weldment was done using different welding speeds of 210 mm/min, 190 mm/min, 170 mm/min and 150 mm/min in a single pass. The welding of speed of 170 mm/min provided the highest aspect ratio compared to all other welding speed and the hot cracks were found at 150 mm/min is due to high input supplied at the lowest speed. The poor depth of penetration was found at the welding speeds of 210 mm/min and 190 mm/min, because of insufficient heat input available for keyhole to penetrate other side. The maximum Vicker's microhardness was observed at the welding speed of 210 mm/min and lowest value is determined at 150 mm/min. Also, the results revealed that the value of microhardness is inversely related to the welding speed. The welding of 170 mm/min has given best quality of welding considering aspect ratio and near highest value of microhardness. It can be considered as the optimum welding speed for the welding of hastelloy X plate in K-PAW